The other asian enigma: Explaining the rapid reduction of undernutrition in Bangladesh - Headey, Derek D.; Hoddinott, John F.; Ali, Disha; Tesfaye, Roman; Dereje, Mekdim (International Food Policy Research Institute, 2014)
South Asia has long been synonymous with persistent and unusually high rates of child undernutrition—the so-called Asian enigma. Yet contrary to this stereotype, Bangladesh has managed to sustain a rapid reduction in the rate of child undernutrition for at least two decades. In this paper we aim to understand the sources of this unheralded success with the aspiration of deriving policy-relevant lessons from Bangladesh’s experience. To do so we employ a regression analysis of five rounds of Demographic and Health Surveys covering the period from 1997 to 2011.